374 Multi-omic Analysis Identifies a SPAK Kinase-regulated Ensemble of Choroid Plexus Ion Transport Proteins Relevant for Post-infectious Hydrocephalus. (1st April 2022) - Robert, Stephanie; Reeves, Benjamin; Karimy, Jason K.; Marlier, Arnaud; Kiziltug, Emre; DeSpenza, Tyrone; Singh, Amrita; Allington, Garrett; Phan, Duy; Zhang, Jinwei; Kahle, Kristopher Thomas
Abstract : INTRODUCTION: Postinfectious hydrocephalus (PIH) is the most common cause of acquired hydrocephalus worldwide. Treatment is typically through CSF diversion via ventriculoperitoneal shunting, which has high rates of morbidity and is often unavailable in developing countries. METHODS: SPAK knockout (KO) rats were generated using Crispr/CAS9. Control and SPAK KO male rats were implanted with an infusion catheter to introduce E. coli (genetically engineered +/-LPS) or LPS into the lateral ventricles over 72 hours. CSF secretion was measured by catheter placement into the lateral ventricle, and ventricular size by MRI. ChP were harvested for immunohistochemistry (IHC), western blot (WB), genomic/proteomic analysis, and single-cell RNA sequencing (scRNAseq). To investigate SPAK-associated ChP targets, we purified the SPAK-protein complex, identified physical interactors using liquid chromatography/dual mass spectroscopy (LC-MS/MS), and validated top candidates by WB/IHC. RESULTS: Robust bumetanide-sensitive, SPAK-dependent, CSF hypersecretion and ventriculomegaly was observed and dependent on the presence of LPS. LPS triggered significant up-regulation of activating SPAK phosphorylation (Thr233/185), and the bumetanide-sensitive cation-chloride cotransporter NKCC1 (Thr203/207/212). LC-MS/MS pull-down assay additionally revealed three other important SPAK-bound ion transporters, alpha-1 subunit of Na/K ATPase, K+ channel KCNJ13/Kir7.1, and Cl- channel CLIC6. All SPAK-bound targets co-localized with pSPAK at the ChP apical membrane in LPS conditions. This interaction, as well as CSF hypersecretion and ventriculomegaly, were abrogated in LPS-treated SPAK KO animals. CONCLUSION: Multi-omic analysis identified a SPAK-regulated ensemble of ion transport proteins relevant for PIH at the ChP apical membrane. Given the recent development of SPAK kinase inhibitors, our findings uncover a targetable mechanism for the pharmacological treatment of PIH and potentially other forms of inflammation-associated acquired hydrocephalus.